Inflences of Mn2+ ions, and Mn2+–Yb3+ dimer on the optical band gaps and bandwidth flatness of near-infrared emissions of Ho3+/Tm3+, Ho3+/Tm3+/Yb3+ co-doped calcium aluminosilicate glasses - Ho Kim Dan (Elsevier, 2022)
2023